A mock circulation loop for in vitro haemodynamic evaluation of aorta. (July 2020) - Li, Xuhui; Li, Zhenfeng; Chen, Duanduan
Abstract: Haemodynamic conditions play a crucial role in the pathological development of aortic dissection (AD). However, it is challenging to quantitatively and precisely capture the flow features in vivo. In this study, a mock circulation loop (MCL) embedded with patient-specific aortic phantoms was proposed. In order to evaluate perfusion characters, a normal aortic model and an AD model were established with twelve main branches. The system is capable of replicating the aortic geometry, vascular compliance, characteristic resistance, and peripheral resistance of the cardiovascular system. By altering controlling parameters, it can mimic various cardiovascular conditions. The physiological healthy rest cardiac condition was reproduced and the rationality and accuracy of the system was confirmed by comparing the measured flow data from the MCL with a normal aortic phantom and the in vivo ultrasound velocimetry of healthy volunteers (maximum discrepancy was 4.69%). Different flow features between the normal and AD phantoms were quantitatively compared by pressure sensors and ultrasonic flow sensors under the same condition. Therefore, the proposed MCL can be applied as a research tool for in vitro haemodynamic analysis of the aorta. Moreover, it can be applied to evaluate the performance of interventional devices and to provide a realistic platform for trainings on interventional treatments.